2020
DOI: 10.1038/s41375-020-0940-8
|View full text |Cite
|
Sign up to set email alerts
|

N-glycosylation of monoclonal light chains on routine MASS-FIX testing is a risk factor for MGUS progression

Abstract: Our group previously demonstrated that M-protein light chain (LC) glycosylation can be detected on routine MASS-FIX testing. Glycosylation is increased in patients with immunoglobulin light chain amyloidosis (AL) and rarely changes over the course of a patient’s lifetime. To determine the rates of progression to AL and other plasma cell disorders (PCDs), we used residual serum samples from the Olmsted monoclonal gammopathy of undetermined significance (MGUS) screening cohort. Four-hundred and fourteen patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 20 publications
(8 reference statements)
4
49
0
Order By: Relevance
“…We confirm the findings of previous studies demonstrating high rates of LC N-glycosylation in CAD and AL amyloidosis 5,6,8 . We expand upon previous work in identifying additional PCD with LC N-glycosylation, including cryoglobulinemia, plasmacytoma, and monoclonal immunoglobulin deposition disease.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We confirm the findings of previous studies demonstrating high rates of LC N-glycosylation in CAD and AL amyloidosis 5,6,8 . We expand upon previous work in identifying additional PCD with LC N-glycosylation, including cryoglobulinemia, plasmacytoma, and monoclonal immunoglobulin deposition disease.…”
Section: Discussionsupporting
confidence: 92%
“…Of those who were evaluated, approximately half had a FA and two thirds had a BMB performed, which have individual sensitivities of 70-75% and combined sensitivities of 85-90% for the diagnosis of AL amyloidosis 16 . Follow-up on these patients is short, but prior studies have shown that patients with MGUS and N-glycosylation have a sixfold higher rate of progression to a malignant PCD than their non-glycosylated counterparts 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previously underappreciated finding of M-proteins when employing the intact LC method was the observation of M-proteins with a LC mass that was broad and outside the normal mass ranges of kappa and lambda LCs 25 , 28 , Additional studies demonstrated that these LCs contained N-linked glycosylation and were to be more prevalent in patients with AL-amyloidosis 37 and cold agglutinin disease 38 than other PCDs. Interestingly, LC glycosylation was also found to be an independent risk factor for the progression of MGUS to myeloma and related disorders 39 . These glycosylated LCs were demonstrated to be present years before the diagnosis of myeloma of related disorder and hence may allow for identification of patients at higher risk for PCDs 40 .…”
Section: M-protein Detection By Mass Spectrometrymentioning
confidence: 99%
“…In recent years, advanced molecular characterization of M‐proteins has become more commonplace with the advent of a routine mass spectrometric assay for M‐protein detection, characterization, and monitoring 11–16 . This assay is able to detect immunoglobulin modifications that are associated with specific disease processes, such as LC glycosylation, which is predictive of progression to AL amyloidosis and other plasma cell disorders 15,17 . Recently, a population‐based cohort study of patients with IgM M‐protein of undetermined significance (MGUS) demonstrated that patients with a clinical diagnosis of CAD were more likely to have M‐protein LC glycosylation than those without such a diagnosis 18 …”
Section: Introductionmentioning
confidence: 99%